Возможности реализации механохимических явлений в производстве строительных силикатных композитов - Шинкевич, Е. С.; Луцкин, Е. С.; Бондаренко, Г. Г.; Доценко, Ю. В. (НТУ "ХПИ", 2009)
Традиційно термічна активація компонентів силікатобетонної суміші здійснюється в автоклавах, де в умовах підвищеної температури і тиску відбувається гідротермальний синтез гідросилікатів кальцію. На основі експериментально-теоретичних досліджень обґрунтована можливість отримання силікатних матеріалів неавтоклавного тверднення методом литтєвого формування силікатобетонних механохімічно активованих сумішей.

Traditionally thermal activation of components lime-silica mixes is carried out in autoclaves where in conditions of the raised temperature and pression there is a hydrothermal synthesis of hydrosilicates of calcium. On the basis of the opportunity of reception of silicate materials non-autoclave hardening by a method molding formations lime-silica mechano-chemistry activated mixes is experimentally-theoretical studies proved.
Keywords: литьевая технология; силикатобетонная смесь; вязкость; мелкозернистый заполнитель; гидросиликаты